Contralateral Breast Augmentation in Heterologous Breast Reconstruction - Persichetti, Paolo; Cagli, Barbara; Tenna, Stefania; Piombino, Luca; Cogliandro, Annalisa; Iodice, Antonio; Aveta, Achille (IntechOpen, 2012)
None